Suppressing vanadium dissolution of V2O5via in situ polyethylene glycol intercalation towards ultralong lifetime room/low-temperature zinc-ion batteries. Issue 40 (8th October 2021) - Lin, Chunfa; Qi, Fenqiang; Dong, Huilong; Li, Xiao; Shen, Chunping; Ang, Edison Huixiang; Han, Yuqiang; Geng, Hongbo; Li, Cheng Chao
Abstract : The polyethylene glycol pre-intercalated vanadium oxide composites deliver superior zinc-ion storage properties with high specific capacity, stable cycling capability, excellent rate and low-temperature performance. Abstract : Zinc-ion batteries (ZIBs) are a main focus worldwide for their potential use in large-scale energy storage due to their abundant resources, environmental friendliness, and high safety. However, the cathode materials of ZIBs are limited, requiring a stable host structure and fast Zn 2+ channel diffusion. Here, we develop a strategy for the intercalation of polyethylene glycol (PEG) to facilitate Zn 2+ intercalation and to suppress the dissolution of vanadium in V2 O5 . In particular, PEG-V2 O5 shows a high capacity of 430 mA h g −1 at a current density of 0.1 A g −1 as well as excellent 100 mA h g −1 specific capacity after 5000 cycles, with a high current density of 10.0 A g −1 . A reversible capacity of 81 mA h g −1 can even be achieved with a low temperature of −20 °C at a current density of 2.0 A g −1 after 3500 cycles. The superior electrochemical performance comes from the intercalation of PEG molecules, which can improve kinetic transport and structural stability during the cycling process. The Zn 2+ storage mechanism, which provides essential guidelines for the development of high-performance ZIBs, can be found through various ex situ characterization technologies and density functional density calculations.